PENULISAN LITERATUR DAN PRAKTIK SITASI DALAM PENELITIAN ILMIAH: MENUJU PENULISAN YANG TERSTRUKTUR, AKADEMIK, DAN BEBAS PLAGIARISME - Ningsih, Devi Sri Cahya; Hayadi, B. Herawan; Salbiah, Siti; Ma’arif, Tubagus Maharm; Rukiyah, Rukiyah; Samsuri, Samsuri (STAI Darul Qalam Tangerang, 2026)
The systematic organization of literature and consistent citation practices constitute two fundamental pillars in the preparation of high-quality scientific research articles, particularly for journals indexed in Scopus. This article discusses how researchers can structure literature reviews thematically, select credible sources, and apply accurate citation techniques to avoid plagiarism while strengthening the legitimacy of research findings. Effective literature writing does not merely compile previous research results; rather, it demonstrates critical synthesis, reconciles differing findings, and identifies research gaps that serve as the basis for justifying the current study. Proper citation practices include the use of clear paraphrasing, accurate citation placement (both in-text and in the reference list), and consistency in citation style (e.g., APA 7th edition) in accordance with journal guidelines. This article emphasizes that citation is not merely a technical formality; instead, it represents a means for authors to engage in scholarly dialogue with the academic community, construct a coherent knowledge narrative, and demonstrate academic integrity. Researchers are also encouraged to utilize reference management software, such as Mendeley or Zotero, to ensure accuracy and efficiency in literature writing and citation practices. By adhering to these principles, authors can enhance the readability, credibility, and publication potential of their articles in reputable international journals while minimizing the risk of academic ethical violations.